Proposed Diagnostic Criteria for Invasive Pulmonary Aspergillosis in Patients with Autoimmune Inflammatory Rheumatic Diseases: A Proof-of-Concept Study - Takashi Kurita; Koh Okamoto; Noritaka Sekiya; Ryoichi Hanazawa; Akio Yamamoto; Tadashi Hosoya; Akihiro Hirakawa; Shinsuke Yasuda; Yoshiaki Gu (Journal of Fungi, 2025)
The EORTC/MSGERC definition lacks sufficient sensitivity for diagnosing invasive pulmonary aspergillosis (IPA) in patients with autoimmune inflammatory rheumatic diseases (AIIRDs). We hypothesized that the partial fulfillment of the EORTC/MSGERC definition can improve its diagnostic sensitivity. This retrospective observational study included patients with AIIRDs on immunosuppressive therapy who underwent serum galactomannan antigen testing for suspected IPA. Patients who fulfilled the clinical features or mycological evidence as per the EORTC/MSGERC definition were considered as having “potential IPA.” We compared the clinical characteristics of 364 patients who were categorized into 3 groups—potential IPA (n = 29), proven/probable IPA (n = 24), and non-IPA (n = 311; not meeting any definition). The potential and proven/probable IPA groups had significantly lower survival rates than the non-IPA group (p < 0.001). The potential IPA (adjusted hazard ratio [aHR], 2.0; 95% confidence interval [CI], 1.1–3.8) and proven/probable IPA (aHR, 2.6; 95% CI, 1.4–4.9) were independent risk factors for mortality. Compared with the EORTC/MSGERC definition, our proposed criteria improved sensitivity based on the diagnosis at the end of observation (50.0%, 100.0%, respectively). The characteristics and mortality rates of patients were similar between the potential and proven/probable IPA groups. Using these criteria for clinical diagnosis may provide high sensitivity.